Faktor-Faktor Yang Mempengaruhi Gangguan Psikotik Pada Ibu Hamil - Suryanti S; Sitti Nurana; Nurlina Akbar (PT.Mantaya Idea Batara, 2025)
Background: Psychotic disorders are one of the serious mental health problems, particularly among pregnant women. Various factors, both biological and psychosocial, are suspected to play a role in influencing the occurrence of psychotic disorders during pregnancy. However, to date, evidence regarding the most influential factors remains inconsistent. This study aims to analyze the factors affecting psychotic disorders in pregnant women..Method: The study used a quantitative design with a cross-sectional approach. A total of 72 pregnant women who attended antenatal care at the Rappokalling Health Center in Makassar City were selected as respondents. Data were collected using a structured questionnaire and analyzed using the chi-square test to assess the relationship between independent variables and psychotic disorders..Result: The analysis showed no significant relationship between age (P-value = 0.7), education (P-value = 0.8), parity (P-value = 0.1), gestational age (P-value = 0.3), employment status (P-value = 0.1), family income (P-value = 0.2), knowledge (Pvalue = 0.08), and social support (P-value = 0.1) with psychotic disorders in pregnant womenConclusion: This study concludes that factors such as age, education, parity, gestational age, employment status, family income, knowledge, and social support do not have a significant relationship with psychotic disorders in pregnant women in the population studied.